2019
DOI: 10.3928/23258160-20191031-07
|View full text |Cite
|
Sign up to set email alerts
|

En Face OCT of Type 2 Neovascularization:A Reappraisal of the Pitchfork Sign

Abstract: BACKGROUND AND OBJECTIVES: To describe a new en face optical coherence tomography (OCT) imaging feature of type 2 choroidal neovascularization (CNV) and illustrate the OCT angiographic (OCTA) findings in these eyes. PATIENTS AND METHODS: Multimodal images of patients with type 2 CNV who displayed the typical “pitchfork” sign with cross-sectional OCT were reviewed. Corresponding en face structural OCT and OCTA images were analyzed to correlate the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This seemed to confirm the usefulness of this sign to distinguish iCNV from AMD-CNV, as previously reported. 16–18 However, multiple linear regression analysis found no significant effect of the lesion type on the PFS prevalence after accounting for the subject age, and subjects with PFS were significantly younger than those without it in all groups. Furthermore, the presence/absence of a PFS did not affect the odds for a specific diagnosis in the logistic regression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This seemed to confirm the usefulness of this sign to distinguish iCNV from AMD-CNV, as previously reported. 16–18 However, multiple linear regression analysis found no significant effect of the lesion type on the PFS prevalence after accounting for the subject age, and subjects with PFS were significantly younger than those without it in all groups. Furthermore, the presence/absence of a PFS did not affect the odds for a specific diagnosis in the logistic regression.…”
Section: Discussionmentioning
confidence: 92%
“…11 However, the PFS has also been described in CNV related to noninflammatory conditions, making the specificity of this sign a topic of debate. 5,18 There is a need to identify features on OCT that can help in differentiating CNV related to conditions such as AMD, uveitis, and myopia, the three most common causes. In this study, we have analyzed the OCT features from a large cohort of patients with iCNV, myopic CNV, and AMD-related CNV to characterize the specific OCT features that can help in identifying the underlying etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Recent evidence, however, suggests that the pitchfork sign may not be specific to inflammatory type 2 CNV. 40,41 Disorders Relating to Toxicity Flying saucer sign. The flying saucer sign was first described by Chen et al 42 in patients with suspected hydroxychloroquine retinopathy.…”
Section: Age-related Macular Degeneration-related Disordersmentioning
confidence: 99%
“…Various retinal pathologies including macular hole, subhyaloid hemorrhage, sub-internal limiting membrane (sub-ILM) hemorrhage and outer retinal disruption following laser pointer injury have been described [78,79]. However, reports of laser pointer induced CNV are sporadic [80]. Fujinami et al [81] reported on an intellectually disabled child who suffered from CNV following presumably frequent and repeated exposure to a laser pointer as a toy.…”
Section: Handheld Laser Pointersmentioning
confidence: 99%